Multilevel analysis of determinants of anemia among young women (15-24) in sub-Sahara Africa - Misganaw Gebrie Worku; Tesfa Sewunet Alamneh; Achamyeleh Birhanu Teshale; Yigizie Yeshaw; Adugnaw Zeleke Alem; Hiwotie Getaneh Ayalew; Alemneh Mekuriaw Liyew; Zemenu Tadesse Tessema; Getayeneh Antehunegn Tesema (PLoS ONE, 2022)
Background Anemia is a disorder by which the body’s red blood cells are inadequate to fulfill The physiological needs of the body. The World Health Organization (WHO) defines anemia as having a hemoglobin (Hb) level of less than 120 g/l for nonpregnant women and 110 g/l for pregnant women. It has serious implications for human health as well as negative social and economic consequences like decreased workforce, impaired learning, and stunted child development. As these women are highly vulnerable to different micro and macro-nutritive deficiency associated with rapid physical, mental and psychological development, particular attention should be given to a young woman (15–24). Therefore this study assesses the magnitude and determinants of anemia among young women in sub-Saharan Africa (SSA). Methods This was a secondary data analysis based on the Demographic and Health Surveys (DHS) data conducted in sub-Saharan Africa. We pooled the most recent DHS surveys done in 31 sub-Sahara Africa and a total weighted sample of 88, 832 young women (15–24 years) were included. At bivariable analysis, variables with a p-value of ≤0.2 were selected for multivariable analysis, and at the multivariable analysis variables with a p-value of ≤0.05 were considered as a significant factor associated with anemia among young women (15–24 years). Results The pooled prevalence of anemia among young women (15–24) in sub-Sahara Africa was 42.17% [95%CI: 41.85, 42.50]. Young women of aged 20–24 years [AOR = 0.92, 95%CI: 0.89–0.95], women from rich household [AOR = 0.83, 95%CI: 0.80–0.87], young women with primary [AOR = 0.7, 95%CI: 0.67–0.72], secondary [AOR = 0.72, 95%CI: 0.69–0.75] and higher educational status [AOR = 0.58, 95%CI: 0.53–0.64], married women [AOR = 1.12, 95%CI: 1.08–1.17], divorced/separated/widowed women [AOR = 1.16, 95%CI: 1.08–1.25], women who use modern contraceptive [AOR = 0.65, 95%CI: 0.62–0.67], young women who ever had terminated pregnancy [AOR = 1.22, 95%CI: 1.14–1.29], overweight young woman [AOR = 0.79, 95%CI: 0.76–0.82] and young women from female-headed household [AOR = 0.94, 95%CI: 0.91–0.97] were the individual-level factors that significantly associated with anemia of young women. Meanwhile, being a rural dweller [AOR = 0.82, 95%CI: 0.79–0.85] and high community educational level [AOR = 0.87, 95%CI: 0.70–0.97] were the community level determinant of anemia. Interclass correlation coefficient (ICC), Median Odds Ratio (MOR) and Percentage change in variance (PCV) were done for the assessment of the random effect model of the multilevel analysis. The ICC value in the null model was 0.05, which indicates that 5% of the variation in anemia among young women in sub-Saharan Africa was attributed to community-level factors. Conclusion The prevalence of anemia among young women in this study was higher compared with reports from the previous studies. Divorced/separated/widowed women, married women and women with ever terminated pregnancy, young women with primary, secondary and higher educational achievement, being rural dwellers, young women aged 20–24 years, being from rich households and women who used modern contraceptives were factors that significantly associated with anemia among young women. Therefore, particular attention should be given to those higher-risk women including, young women with a history of a terminated pregnancy, those from rural areas and young women aged 15–19 years to reduce the burden of anemia among these young women as the continuity of the future generation depends on the health of young women.